Enhanced high temperature hydrogen permeation characteristics of V-Ni alloy membranes containing a trace amount of yttrium - Oh, Ju-Young; Ko, Won-Seok; Suh, Jin-Yoo; Lee, Youg-Su; Lee, Byeong-Joo; Yoon, Woo Young; Shim, Jae-Hyeok (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The hydrogen permeation behaviors of V85Ni15 and V84.8Ni15Y0.2 membranes with palladium coating layers were compared at 480 degrees C, which is considered high temperature for conventional vanadium alloy-based membranes. Although the hydrogen permeability of the V85Ni15 membrane drastically decreased over time, that of the V84.8Ni15Y0.2 membrane was sustained for 12 days. The role of yttrium in the membrane was to effectively hinder interdiffusion between the Pd coating layers and the V alloy substrate during hydrogen permeation. The results of the present study provide important clues for the development of hydrogen permeable metallic membranes for high temperature applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: INTERMETALLIC DIFFUSION; PD; PURIFICATION; INTERDIFFUSION; PERMEABILITY; SEPARATION; AL; CU